A School Ancient Greek Epic Parody from Kellis - Ermolaeva, Elena (Hyperboreus, 2015)
The miniature codices from Kellis of the 4th c. AD containing an anonymous fragment of Homeric paraphrase or parody were published by C. A. Hope and K. A. Worp in 2006. In this article I discuss the text from Kellis trying to determinate its grammatical, literary, and social aspects, and giving a line-by-line commentary to it. I suppose that the double parody of Homer and of the liturgical Christian texts could be a point of the joke. We can presume following Worp that the audience were students of a school because the wooden codices also contain a list of Greek verbs and mathematical calculations. Τhe parody could be written by a well educated pagan.